Incidence of neonatal respiratory morbidity after vaginal and caesarean delivery in the late-preterm and term period – a retrospective cohort study (Swiss Medical Weekly, 2024)
BACKGROUND: Respiratory distress syndrome is a leading cause of neonatal intensive care unit admissions for late preterm (34–36 weeks gestational age) and term infants (37–41 weeks). The risk for respiratory morbidity appears to increase after an elective caesarean delivery and might be reduced after antenatal corticosteroids. However, before considering antenatal corticosteroids for women at high risk of preterm birth after 34 weeks, the incidence of respiratory distress syndrome and the effect of delivery mode on this incidence requires further evaluation. Therefore, this study aimed to investigate the relationship between respiratory distress syndrome incidence and delivery mode in late preterm and term infants.METHODS: In this retrospective cohort study, the clinical databases of the University Hospitals of Zurich and Basel were queried regarding all live births between 34 + 0 and 41 + 6 weeks. Neonatal intensive care unit admissions due to respiratory distress syndrome were determined and analysed in regard to the following delivery modes: spontaneous vaginal, operative vaginal, elective caesarean, secondary caesarean and emergency caesarean.RESULTS: After excluding malformations (n = 889) and incomplete or inconclusive data (n = 383), 37,110 infants out of 38,382 were evaluated. Of these, 5.34% (n = 1980) were admitted to a neonatal intensive care unit for respiratory distress syndrome. Regardless of gestational age, respiratory distress syndrome in infants after spontaneous vaginal delivery was 2.92%; for operative vaginal delivery, it was 4.02%; after elective caesarean delivery it was 8.98%; following secondary caesarean delivery, it was 8.45%, and after an emergency caesarean it was 13.3%. The risk of respiratory distress syndrome was higher after an elective caesarean compared to spontaneous vaginal delivery, with an odds ratio (OR), adjusted for gestational age, of 2.31 (95% CI 1.49–3.56) at 34 weeks, OR 5.61 (95% CI 3.39–9.3) at 35 weeks, OR 1.5 (95% CI 0.95–2.38) at 36 weeks, OR 3.28 (95% CI 1.95–5.54) at 37 weeks and OR 2.51 (95% CI 1.65–3.81) at 38 weeks. At 39 weeks, there was no significant difference between the risk of respiratory distress syndrome after an elective caesarean vs. spontaneous vaginal delivery. Over the study period, gestational age at elective caesarean delivery remained stable at 39.3 ± 1.65 weeks.CONCLUSION: The incidence of respiratory distress syndrome following an elective caesarean is up to threefold higher in infants born with less than 39 weeks gestational age compared to those born by spontaneous vaginal delivery. Therefore — and whenever possible — an elective caesarean delivery should be planned after 38 completed weeks to minimise the risk of respiratory morbidity in neonates.